Comparison of Debris Extrusion and Preparation Time by Traverse, R-Motion Glider C, and Other Glide Path Systems in Severely Curved Canals - Taher Al Omari; Layla Hassouneh; Khawlah Albashaireh; Alaa Dkmak; Rami Albanna; Ali Al-Mohammed; Ahmed Jamleh (International Journal of Dentistry)
This study evaluated debris extrusion by Traverse and R-Motion Glider C during glide path preparation. Seventy-five mesial roots of mandibular molars with severely curved mesiobuccal canals were distributed into five groups: Traverse, R-Motion Glider C, HyFlex EDM Glidepath, One G, and R-Pilot. During the glide path preparation, debris extruded beyond the apex were collected. The debris weight was calculated (in mg), and the preparation time was recorded (in s). All the systems extruded debris beyond the apex; Traverse extruded the highest amount followed by HyFlex EDM Glidepath, R-Motion Glider C, One G, and R-Pilot (p <0.01). Traverse required almost half the duration of HyFlex EDM Glidepath to prepare the canals (p <0.01), while R-Motion Glider C required the least time (p <0.05). Traverse extruded the highest amount of debris, whilst R-Motion Glider C extruded similar amounts of debris to HyFlex EDM Glidepath, One G, and R-Pilot systems.